The political economy of European cartel regulation - Buch-Hansen, Hubert (Politica, 2016)
For many years, cartels were considered a natural and legitimate way of organizing markets throughout Europe. In the past few decades, however, a paradigm shift in the regulatory approach to cartels has taken place, both at national and EU level. This shift is for instance reflected in the increasingly tough sanctions imposed on cartel participants. The article adopts a critical political economy perspective on European cartel regulation and divides its development into two phases; as part of a ”regulated” form of capitalism and as an element in a neoliberal form of capitalism. The paradigm shift is mapped with examples from the EC/EU, Denmark and other European countries and explained with reference to changes in power relations, social structures and accumulation and prevailing ideas. Finally, the article asks whether there are signs that the economic crisis in the wake of the financial crisis in 2008 will cause a new shift in the way cartels are regulated in Europe.